2022
DOI: 10.3389/fpubh.2022.829840
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting Cancer-Specific Survival in Children With Wilms Tumor: A Study Based on SEER Database and External Validation in China

Abstract: BackgroundWilms tumor (WT) is the most common tumor in children. We aim to construct a nomogram to predict the cancer-specific survival (CSS) of WT in children and externally validate in China.MethodsWe downloaded the clinicopathological data of children with WT from 2004 to 2018 in the SEER database. At the same time, we used the clinicopathological data collected previously for all children with WT between 2013 and 2018 at Children's Hospital of Chongqing Medical University (Chongqing, China). We analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The low level of granularity with respect to sociodemographic factors in SEER also hinders our ability to draw inferences about actionable disparities in WT outcomes. A comparative study of children with WT in China versus the United States between 2004 and 2018 showed that older age was associated with poorer survival only in the United States 34. Congruent with our study’s finding of younger age at diagnosis among AAAP patients (Table 3), the patients in China tended to receive WT diagnosis at a younger age.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…The low level of granularity with respect to sociodemographic factors in SEER also hinders our ability to draw inferences about actionable disparities in WT outcomes. A comparative study of children with WT in China versus the United States between 2004 and 2018 showed that older age was associated with poorer survival only in the United States 34. Congruent with our study’s finding of younger age at diagnosis among AAAP patients (Table 3), the patients in China tended to receive WT diagnosis at a younger age.…”
Section: Discussionsupporting
confidence: 41%
“…Though, management uniformity across populations can be called into question, as the Chinese cohort had less advanced disease, smaller sample size, and shorter follow-up, yet displayed much worse survival. 34 Because of improvement in risk stratification and treatment advances over recent decades, WT has transformed from a disease with dismal recurrence and survival rates to a disease for which long-term cure is common and expected. This study contributes to a growing body of evidence that older age of WT diagnosis is an independent negative prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To aid in this endeavor, prognostic models specific to patients with advanced malignancies receiving palliative RT have emerged [26,27]. Numerous pediatric-specific prognostic models are available for specific malignancies [28–30] and intensive care admissions [31]. We were only able to identify one model for children referred to a palliative care service that was able to predict probability of 60-day survival based on a number of variables [32].…”
Section: Estimating Prognosismentioning
confidence: 99%
“…Studies have shown that clinicopathological factors such as gender, tumor side, tumor size, and surgical approach significantly correlate with the prognosis of elderly patients with RCC (8)(9)(10). Wang et al found that race, tumor histological type, histological grade, T stage, N stage, tumor size, surgery, radiotherapy, and chemotherapy were independent risk factors for distant metastasis of elderly RCC (35,155,365) (11).…”
Section: Introductionmentioning
confidence: 99%